Effectiveness of Implementing No Smoking Area (KTR) Policy in Subulussalam City Area - Nurdin, Ambi; Usman, Bukhari; Fuadi, Zahrul; Mulyadi, Mulyadi; Yusuf, Muhammad (Teewan Journal Solutions, 2025)
This article presents a comprehensive review of the implementation of the Smoke-Free Area (KTR) Policy in Subulussalam City as a proactive step by the City Government in realizing a healthier and better quality environment for all its citizens. This KTR Policy is designed not only to minimize the negative impacts of exposure to cigarette smoke, both for active smokers and vulnerable passive smokers, but also as a vital instrument to encourage changes in community behavior towards a healthier and smoke-free lifestyle. The urgency of implementing KTR in Subulussalam is analyzed from various crucial dimensions, including: (1) Protection of Public Health by reducing the risk of cigarette-related diseases; (2) Improving Air Quality in public spaces; (3) Encouraging Sustainable Healthy Living Behavior; (4) Creating a Comfortable Environment in public facilities; and (5) Support for Sustainable Development by improving public health. This article also specifically details the areas that are legally designated as Smoke-Free Areas in Subulussalam, including but not limited to: health care facilities (hospitals, health centers), places of learning (schools, campuses), places of worship, children's play areas, sports facilities, public transportation, workplaces, and other public facilities stipulated by local regulations. Although the implementation of KTR faces significant challenges such as the need for continuous massive socialization, consistent supervision, and effective law enforcement, the success of this policy is expected to significantly improve the quality of life and health of the community, and become an important foundation for the progress and prosperity of Subulussalam City in the future. This article emphasizes that KTR is a long-term investment for collective health and better city development.